The Wise Merchant - Barlaeus, Caspar (Amsterdam University Press, 2019)
On 9 January 1632, at the inauguration of the Amsterdam Illustrious School - the predecessor of the city's university - Caspar Barlaeus delivered a speech that has continued to arouse the curiosity of researchers and the general public alike: Mercator sapiens. This famous oration on the wise merchant is now considered a key text of the Dutch Golden Age. At the same time it is surrounded by misunderstandings regarding Barlaeus himself, the nascent Illustrious School, and Amsterdam's merchant culture. This volume presents the first English translation and the first critical edition of the Mercator sapiens, preceded by an introduction providing historical context and a fresh interpretation of this intriguing text.Anna-Luna Post and Corinna Vermeulen shed new light on the roles of humanist scholarship and rhetoric in Holland's metropolis. Caspar Barlaeus's 1632 oration, The Wise Merchant, has often been cited but seldom read. Their edition, translation and introduction set the work into its historical context with learning, clarity and economy. - Anthony Grafton